Archaeometric characterization of black gloss ware from Populonia (Tuscany): Imported pottery and local production of the Petites Estampilles Group. (February 2022) - Pagliantini, Laura; Madrid i Fernández, Marisol; Bernard, Seth; Camporeale, Stefano; Mascione, Cynthia; Buxeda i Garrigós, Jaume; Sinner, Alejandro G.
Highlights: Archaeometric study reveals four categories of black gloss ware at Populonia's acropolis site. Locally produced black gloss ware identified with early Petites Estampilles Group. Production map of Petites Estampilles Group extended significantly to North Etruria. Abstract: This paper presents a chemical characterization by means of WDXRF and mineralogical characterization by means of XRD of 21 individuals of black gloss pottery from the excavations on the acropolis of Populonia. The results shed new light on the circulation of pottery to this major urban centre in North Etruria during the Roman Republican period, while they also suggest the likelihood of local manufacture. In particular, we identify at Populonia four different black gloss productions that can be archaeometrically defined as Campanian A, Volterra, Etrusco-Latial 1 and a possible local production of ceramics belonging to the Petites Estampilles Group, active in the late fourth and third centuries BCE. Once thought to be a workshop located at Rome itself, this class is now understood as a diffuse network of workshops located in South Etruria and Latium producing pottery of similar technology and style. The present study potentially extends the map of its production to North Etruria in a region at that time newly incorporated into the expanding Roman Republican empire.